Synergies between the key biodiversity area and systematic conservation planning approaches. Issue 1 (17th December 2018) - Smith, Robert J.; Bennun, Leon; Brooks, Thomas M.; Butchart, Stuart H.M.; Cuttelod, Annabelle; Di Marco, Moreno; Ferrier, Simon; Fishpool, Lincoln D.C.; Joppa, Lucas; Juffe‐Bignoli, Diego; Knight, Andrew T.; Lamoreux, John F.; et al.
Abstract: Systematic conservation planning and Key Biodiversity Areas (KBAs) are the two most widely used approaches for identifying important sites for biodiversity. However, there is limited advice for conservation policy makers and practitioners on when and how they should be combined. Here we provide such guidance, using insights from the recently developed Global Standard for the Identification of KBAs and the language of decision science to review and clarify their similarities and differences. We argue the two approaches are broadly similar, with both setting transparent environmental objectives and specifying actions. There is however greater contrast in the data used and actions involved, as the KBA approach uses biodiversity data alone and identifies sites for monitoring and vigilance actions at a minimum, whereas systematic conservation planning combines biodiversity and implementation‐relevant data to guide management actions. This difference means there is much scope for combining approaches, so conservation planners should use KBA data in their analyses, setting context‐specific targets for each KBA type, and planners and donors should use systematic conservation planning techniques when prioritizing between KBAs for management action. In doing so, they will benefit conservation policy, practice and research by building on the collaborations formed through the KBA Standard's development.